Noncompliance open-bite treatment with Zygomatic anchorage - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2007)
Objective: To evaluate the dentoalveolar and skeletal effects of the new-generation open-bite appliance. Subjects and Methods: The study group was composed of 11 subjects with a mean age of 19.5 years who underwent intrusion of the posterior dentoalveolar segment using an open-bite appliance supported by bilateral zygomatic implants. The study was carried out on lateral cephalograms of the subjects taken before treatment and after intrusion. The mean intrusion time was 9.6 months. Results: The mean intrusion measured as the distance of the U6 to the palatal plane was 3.6 +/- 1.4 mm (P < .001). This resulted in an average of 3.0 degrees +/- 1.5 degrees of closure of the Go-Gn-SN angle (P < .001). The gain in the overbite was 5.1 +/- 2.0 mm (P < .001), and the overjet was reduced by 1.4 +/- 1.5 mm (P < .01). The change in the occlusal plane angle was an average of 2.4 degrees +/- 1.4 degrees counterclockwise rotation (P < .001). The lower facial height was also decreased significantly by 2.9 +/- 1.3 mm (P < .001). No significant changes were observed in the SNA angle and incisor positions (P > .05), except for the interincisal angle, which was increased by 3.5 degrees (P < .05). Conclusion: Zygomatic anchorage can be used effectively for open-bite correction through posterior dentoalveolar intrusion.
Keywords: open bite; Zygomatic anchorage; posterior dentoalveolar intrusion; LONG-TERM STABILITY; SKELETAL ANCHORAGE; CEPHALOMETRIC EVALUATION; ORTHODONTIC ANCHORAGE; ENDOSSEOUS IMPLANTS; TITANIUM SCREWS; INTRUSION; MOLARS; PLACEMENT; REGION